Efficacy of Shexiang Tongxin Dropping Pills in a Swine Model of Coronary Slow Flow - Bai, Yupeng; Zhang, Mingjing; Peng, Sheng; Wang, Yuting; Gu, Ye; Fang, Qianqian; Hu, Liqun (Frontiers in Physiology, 2022)
Objective: Preliminary clinical studies have confirmed that Shexiang Tongxin dropping pills (STDPs) could improve angina pectoris and attenuate vascular endothelial dysfunction in patients with slow coronary flow, but the underlying mechanism is not fully unclear. We aimed to investigate the impact of STDP in a swine model of coronary slow flow (SF) and related mechanisms. Methods: SF was induced by coronary injection of 40μm microspheres, and pigs were randomly divided into the SF group and SF plus STDP group. Pigs in the STDP group received sublingual STDP for 10 min, followed by 1 g STDP oral administration daily for 6 days. Coronary angiography was performed, the TIMI frame count (TFC) was determined, and hemodynamic measurements were performed before, at 30 min, and 7 days post-SF. Serum levels of total NO, NOS, ET-1, C-TNI, and BNP were measured. Myocardial expressions of TNF and IL-6, eNOS, VEGF, CD31, and α-SMA were analyzed by immunohistochemistry and Western blotting. Results: Compared to the SF group, LVEF and TFC were significantly improved at 7 days post-SF in the STDP group. The serum ET-1 level was significantly reduced at 7 days, and NO and NOS levels were significantly higher in the STDP group. Seven days post-SF, myocardial TNF and IL-6 expressions were significantly downregulated, while the expressions of eNOS and VEGF, CD31, and ɑ-SMA were significantly upregulated in the STDP group. Conclusion: Our results showed that STDP improved cardiac function and coronary flow, possibly through reducing inflammatory responses and upregulating myocardial eNOS and VEGF, CD31, and the ɑ-SMA expression.